Perancangan Aplikasi Sistem Pakar Untuk Mendiagnosa Kerusakan Kendaraan Toyota Inova Pada PT. Bengawan Abadi Motor Surakarta - Dwi Rahman, Didik Nugroho, Wawan Laksito (STMIK Sinar Nusantara, 2013)
Purpose of making an expert system application that can Toyota used for junior technicians to analyze damage to toyota inova so that time and energy in a more effective and efficient repairs. Data collection methods include field studies conducted by the authorand literature study. Field studies include observational methods ordirect observation and direct interviews with therelated to the problems examined in order to obtain the data and information would be credible. While the study of literature useful to obtain a theoretical basis that expert opinion about the research object.Data were analyzed with qualitatif and quantitative analysis, the analysis of data showed that in PT. Bengawan Abadi Motor Surakarta common throble or keruskan on Toyota inova car. Qualified personnel available limited, so that the amount of the damage is not possiblesenior technician performed all, inevitably junior technician should also working. Junior technician in doing this damage should be open very thick guidebook or ask senior technicians soless effective. So it needs to be made an expert system to help technicians juniors in diagnosing damage to vehicles Toyota inova Keywords: quantitative analysis, expert system, analyze demage, Toyota Innova